1
$\begingroup$

It is known that the sum of the squared inverses of the divisors satisfies $$\sum _{n \leq x} \sigma_{-2}(n) = \zeta(3)x + \mathcal O(1).$$ On the other hand, an alternate calculation gives me another answer:

$$\begin{align*} \sum _{n \leq x} \sigma_{-2}(n) &= \sum _{a \leq x} \sum _{b \leq \frac xa} \frac 1{b^2}\\ & = \sum _{a \leq x} \left( -\frac ax + \zeta (2) + \mathcal O(\frac {a^2} {x^2}) \right) \\ &= -\frac 1x \left(\frac 12 x^2+ \mathcal O (x)\right) + \zeta(2)x + \frac 1 {x^2}\mathcal O (\sum _{a \leq x }a^2)\\ &= -\frac 12 x + \mathcal O(1) +\zeta(2) x + \frac 13 x + \mathcal O(1). \end{align*}$$

And this is a contradiction. I cannot spot the error in my calculation. Where did it go wrong?

Proof of known asymptotic

$$\begin{align*} \sum _{n \leq x} \sigma_{-2}(n) &= \sum _{a \leq x} \frac 1{a^2} \sum _{b \leq \frac xa} 1\\ & = \sum _{a \leq x} \frac 1 {a^2} \left(\frac xa + \mathcal O(1)\right) \\ &= x \sum_{a \leq x }\frac 1 {a^3} + \mathcal O(\sum _{a \leq x} \frac 1 {a^2}) \\&= \zeta(3)x + \mathcal O(1). \end{align*}$$

$\endgroup$
  • 1
    $\begingroup$ Can you give a link to the "known" result with $\zeta(3)x+O(1)$? $\endgroup$ – Dietrich Burde Sep 26 '18 at 14:03
  • $\begingroup$ @DietrichBurde Hi, I don't have a link but the proof is short. Added it in text. $\endgroup$ – Emolga Sep 26 '18 at 14:23
  • $\begingroup$ @DietrichBurde Found a link: en.wikipedia.org/wiki/… $\endgroup$ – Emolga Sep 26 '18 at 15:05
2
$\begingroup$

You are tacitly assuming that a constant is $1$, while that is not the case.

$$ \sum_{b\leq N}\frac{1}{b^2} = \zeta(2)-\frac{1}{N}+\frac{1}{2N^2}-\frac{1}{6N^3}+\frac{1}{30N^5}+\ldots $$ hence by replacing $N$ with $\frac{x}{a}$ we get $$ \sum_{b\leq\frac{x}{a}}\frac{1}{b^2} = \zeta(2)-\frac{a}{x}+\frac{a^2}{2x^2}-\frac{a^3}{6x^3}+\frac{a^5}{30x^5}+\ldots $$ and summing both sides over $a\leq x$ we have

$$ \sum_{a\leq x}\sum_{b\leq\frac{x}{a}}\frac{1}{b^2} = x\left(\zeta(2)-\frac{1}{2}+\frac{1}{6}-\frac{1}{24}+\frac{1}{180}+\ldots\right)+\mathcal{O}(1) $$ where by the Euler-Maclaurin summation formula the involved constant is exactly $\zeta(3)$ and not $\zeta(2)-\frac{1}{6}$.

$\endgroup$
  • $\begingroup$ Thank you very much! So in other words, the issue hid in my last equality, where I actually had a term $\frac 1 {x^2} \mathcal O(x^3) = \mathcal O(x)$ that absorbed the hidden constant. $\endgroup$ – Emolga Sep 26 '18 at 16:58
  • $\begingroup$ @Emolga: precisely. $\endgroup$ – Jack D'Aurizio Sep 26 '18 at 17:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.